Making sense of Theoretical and Conceptual Frameworks : A C.O.S.T.A. Research Coaching Tool - Costa, King (My University, 2020)
Theoretical and conceptual frameworks play a critical role in building up one’s research study trajectory. Researchers need to decide the foundational dynamics of their research inquiry, right from breaking down concepts from the research questions, to formulation of hypothesis/assumptions and deciding on the philosophical basis for the inquiry. It can therefore be asserted that role theory plays is essential in creation of boundaries and shape for the research inquiry.
Keywords: theoretical framework; Conceptual framework; C.O.S.T.A